Introduction to food engineering / R Paul Singh; Dennis R Heldman - Singh, R. Paul
"Long recognized as the bestselling textbook for teaching food engineering to food science students, this 5th edition transitions with today's students from traditional textbook learning to integrated presentation of the key concepts of food engineering. Using carefully selected examples, Singh and Heldman demonstrate the relationship of engineering to the chemistry, microbiology, nutrition and processing of foods in a uniquely practical blend. This approach facilitates comprehensive learning that has proven valuable beyond the classroom as a lifetime professional reference. Key features in this edition: key concepts now communicated using audio, video, and animations; integrates interactive tools to aid in understanding complex charts and graphs; features virtual experiments of selected food processing operations; videos demonstrating key processes and engineering in practice; presents a practical, unique and challenging blend of principles and ap plication for comprehensive learning. Authors Singh and Heldman use their many years of teaching to present food engineering concepts in a logical progression that covers the standard course curriculum making it easily adaptable for each classroom"